Schwarzian derivative and Janowski convexity - BOHRA, Nisha; RAVICHANDRAN, V. (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
Sufficient conditions relating the Schwarzian derivative to the Janowski convexity of a normalized analytic function f are obtained. As a consequence, sufficient conditions are determined for the function f to be Janowski convex and convex of order α. Also, some equivalent sharp inequalities are proved for f to be Janowski convex. Mathematics Subject Classification (2010): 30C45, 30C80.